In Vitro Propagation of Wild Asparagus adscendens Roxb. using Nodal Explants - Sharma, A. K.; Pandit, J.; Bhardwaj, S. V. (Indian Journal of Hill Farming, 2018)
A rapid and highly effective method for direct regeneration from nodal segments explants was established for Asparagus adscendens Roxb. Nodal segments were inoculated on Murashige and Skoog (MS) medium containing 0.6% agar, 3% sucrose and different combinations of benzylaminopurine (BAP) and kinetin (Kn). Maximum establishment of cultures from nodal explants were obtained on MS medium supplemented with 0.2 mg l-1 BAP and 0.2 mg l-1 Kn. The nodal segments with shoot buds produced maximum number of shoots (5.50 per explant) on MS medium supplemented with 0.05 mg l-1 naphthalene acetic acid (NAA) and 0.3 mg l-1 Kn. The multiplied adventitious shoots were successfully rooted (in vitro) using half strength MS supplemented with 1.0 mg l-1 IBA and 0.3 mg l-1ancymidol, acclimatized and finally transferred to natural conditions.